Dimeric γ-AApeptides With Potent and Selective Antibacterial Activity - Wang, Minghui; Gao, Ruixuan; Sang, Peng; Odom, Timothy; Zheng, Mengmeng; Shi, Yan; Xu, Hai; Cao, Chuanhai; Cai, Jianfeng (Frontiers in Chemistry, 2020)
Over the past few decades, the emergence of antibiotic resistance developed by life-threatening bacteria has become increasingly prevalent. Thus, there is an urgent demand to develop novel antibiotics capable of mitigating this trend. Herein we reported a series of dimeric γ-AApeptide derivatives as potential antibiotic agents with limited toxicity and excellent selectivity against Gram-positive strains. Among them, compound 2 was identified to have the best MICs without inducing drug resistance even after exposure to MRSA for 20 passages. Time-kill kinetics and mechanistic studies suggested that 2 could mimic host-defense peptides (HDPs) and rapidly eradicate MRSA within 2 hours through disturbing the bacteria membrane. Meanwhile, biofilm formation was successfully inhibited even at a low concentration. Taken together, these results suggested the great potential of dimeric γ-AApeptide derivatives as antibacterial agents.